Signatures of Energy Flux in Particle Production: A Black Hole Birth Cry and Death Gasp - Good, Michael R.R.; Ong, Yen Chin (Springer, 2015)
It is recently argued that if the Hawking radiation process is unitary, then a black hole's mass cannot be monotonically decreasing. We examine the time dependent particle count and negative energy flux in the non-trivial conformal vacuum via the moving mirror approach. A new, exactly unitary solution is presented which emits a characteristic above-thermal positive energy burst, a thermal plateau, and negative energy flux. It is found that the characteristic positive energy are and thermal plateau is observed in the particle out fow. However, the results of time dependent particle production show no overt indication of negative energy flux. Therefore, a black hole's birth cry is detectable by asymptotic observers via particle count.
Keywords: physics; energy flux; black holes